STRATEGI PERUSAHAAN UNTUK MEMPERTAHANKAN PELANGGAN HIGH END MARKET DENGAN MENGGABUNGKAN ANALISIS SWOT, BSC, DAN SENI PERANG SUN TZU KE DALAM QFD - , Fidya Savitri, S. T ([Yogyakarta] : Universitas Gadjah Mada, 2011)
Competitive climate in the business environment and telecommunications industries, has spurred the telecommunications operators vying with each other to provide best service to customers, especially enterprise-class customers (enterprise), the incoming group of High-End Market (HEM). They need a lot of choices of telecommunications services to provide solutions to an increasingly complex business needs. Intense competition, especially in segments HEM make Telkom to face competition. This thesis aims to identify strengths and weaknesses, opportunities, and threats (SWOT) for Telkom to face the competition on customers HEM which then results in the point to the four perspectives of balanced scorecard and the order of priority of execution of a management strategy to connect the BSC as "What" and the philosophy of Sun Tzu as "How" in the QFD. Source of research data consisted of analysis of secondary data from journals, books, internet, lecture materials and data related to the company for the proposed research topic and analysis of primary data with focus group and questionnaire by the senior leader (EGM and GM). The results showed that the strategy should be done to strengthen Telkom in tapped opportunities and face threats to the analysis of external factors and shows that companies need to be considered in the implementation of appropriate BSC target can be achieved as closely as possible.